Pembelajaran Fisika Berbasis Collaborative Problem Solving (CPS) untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMA - Salma, Ayudia; Asep Irvan Irvani; Resti Warliani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study examines the effectiveness of the Collaborative Problem Solving (CPS) instructional model in enhancing high school students’ critical thinking skills (CTS) on the topic of sound waves. A quantitative approach was employed, specifically a quasi-experimental design with a pretest–posttest comparison-group arrangement. Participants consisted of two groups selected through purposive sampling: an experimental group with 35 students and a comparison group with 30 students. The primary assessment instrument was a set of essay questions constructed based on the critical thinking criteria proposed by Ennis. The analysis revealed a substantial improvement in students’ CTS within the experimental class following the implementation of the CPS model. A significant difference between the experimental and comparison groups was confirmed using the Mann–Whitney U test, yielding a p-value < 0.001. The effect size of 6.610, as measured by Cohen’s d, is considered large. Consequently, the CPS approach effectively enhanced students’ CTS, particularly in the context of physics learning.